Test Chip Design for Process Variation Characterization in 3D Integrated Circuits - O'Sullivan, Conor (University of Waterloo, 2013)
A test chip design is presented for the characterization of process variations and Through Silicon Via (TSV) induced mechanical stress in 3D integrated circuits. The chip was de- signed, layed-out, and taped-out for fabrication in a 130nm Tezzaron/GlobalFoundries process through CMC microsystems. The test chip takes advantage of the architecture of 3D ICs to split its test structure onto the two tiers of the 3D IC, achieving a device array density of 40.94 m2 per device. The design also has a high spatial resolution and measurement delity compared to similar 2D variation characterization test structures. Background leakage subtraction and radial ltering are two techniques that are ap- plied to the chip's measurements to reduce its error further for subthreshold device current measurements and stress-induced mobility measurements, respectively. Experimental mea- surements are be taken from the chip using a custom PCB measurement setup once the chip has returned from fabrication.
Keywords: 3D; TSV; process variations; Electrical and Computer Engineering